Study of lumbar canal stenosis and its outcome after surgical management in central India - Kariya, Ankur D.; Jain, Pramod A.; Patond, Kisan R. (International Journal of Research in Medical Sciences, 2018)
Background: Lumbar canal stenosis is a painful and potentially disabling condition often encountered in adults. Treatment of lumbar canal stenosis may consist of conservative approach to lumbar canal stenosis consists of rest, lumbar bracing, activity modification and analgesics. Surgical management consists of decompressive laminectomy, laminotomy or facetectomy. In the present study, authors evaluate the outcome in patients of lumbar canal stenosis managed surgically with decompressive laminectomy. Methods: A 50 patients with degenerative lumbar canal stenosis visiting Kasturbha hospital, Sewagram, Wardha from November 2016 to April 2017 were taken up for the study. Patients were taken up for laminectomy and decompression of the affected nerve roots using medial facetectomy. Post operatively patients were regularly followed up at monthly intervals. The ODI score was calculated at the end of 6 months and compared with the baseline score. Results: Fifty patients (mean age-42.9 years) underwent laminectomy and decompression. Baselines ODI score was 71.2±6.4. After 6 month follow up, the score improved significantly to 21±15.6 which was statistically significant. Conclusions: Operative treatment in patients of degenerative lumbar canal stenosis yields excellent functional results as observed based on the ODI score provided case selection is done properly.